The association between academic self‐beliefs and reading achievement among children at risk of reading failure. (3rd March 2014) - Fives, Allyn; Russell, Dan; Kearns, Norean; Lyons, Rena; Eaton, Patricia; Canavan, John; Devaney, Carmel; O'Brien, Aoife
<x xml:space="preserve">Abstract</x> This paper investigates whether children's academic self‐beliefs are associated with reading achievement and whether the relationship is modified by gender and/or age. Data were collected from children at risk of reading failure, that is, emergent readers (6‐ to 8‐year‐olds) in socioeconomically disadvantaged areas reading at a level below the population mean. The authors' own measure of attitude to reading and perceived competence was used. The study found a significant positive association between attitude to reading in class and vocabulary and phonemic awareness and a significant negative association between perceived competence at reading in class and single‐word reading and spelling. Girls' attitude to reading and perceived competence were more positively associated with reading achievement, and this was most evident in the first grade. Perceived competence was inflated among those with the poorest reading and also among boys, in association with reading‐related skills found most challenging by children in this sample.